PELATIHAN MEMBUAT MEDIA DONGENG UNTUK MENANAMKAN PENDIDIKAN KARAKTER DALAM KELUARGA - Sakhi Herwiana; Mukminatus Zuhriyah; Ria Kamilah Agustina (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2021)
The objective of this community service activity / PKM (Pengabdian Kepada Masyarakat) is to provide knowledge to participants (parents and children) about the importance of character education from early age through the family. This program was motivated by problems that happens in society in Ngusikan, Jombang, East Java, children in that area addicted to play gadgets and have a tendency to anti-social behavior and lack of social courtesy. The method in this program used a dialogical collaborative-participatory approach includes in-house training (lectures, questions and answers, discussions) for the delivery of material, direct practice to make storytelling media, testing, practice of using fairy tale media and mentoring assisted by KKNT students. The number of participants in this program is approximately 40 participants, including students. This community service activity (PKM) was followed by women who have job as a housewife. The participants stated that this activity was very useful and was a new experience. This community service activity went well and was greeted with enthusiasm from the participants..